Seismic tests of the structure of rapidly oscillating Ap stars: HR 1217 - Cunha, MS (2003)
HR 1217 is probably the best studied multiperiodic rapidly oscillating Ap star, which makes this star a test case for the seismic analysis of these complex stars. In this paper, we combine the observational data available for HR 1217 and use these data to constrain theoretical models appropriate for this star. In particular, we try to establish which unknown model parameters are the most relevant to reproduce the seismic data. We find that the interior chemical composition has more impact in the theoretical oscillation spectrum of HR 1217 than parameters related to the modelling of convection. Models with lower abundances of heavy elements and larger abundances of helium produce oscillation spectra that are closer to that observed. However, like Matthews et al., we show that it is difficult to find a plausible model that can reproduce the seismic observations of HR 1217, when the uncertainties in the observables are not taken into account, unless a complementary effect is added in order to account for a decrease in the expected large frequency separations.